Misery Has Company: The Shared Emotional Consequences of Everwork Among Women and Men1. Issue 3 (7th May 2018) - Wynn, Alison T.
Abstract : Everwork—defined as a combination of overwork, face time, constant availability, and unpredictability—is becoming an increasingly common form of work, especially among highly skilled service workers. While such an environment would seem to disadvantage mothers in particular, I find that employees of all genders and parental statuses suffer in such intensive work environments. Through 50 in‐depth interviews with management consultants, I examine how employees reconcile their personal lives with the realities of everwork. I characterize young childless men and women as "quit intenders, " mothers as "tightrope walkers, " and fathers as "reluctant sacrificers." This article offers new insight into the tensions employees face between their parenthood ideals and everwork expectations, the strategies they engage in to manage those tensions, and the emotional impacts they experience as a result. Because employees use career–life strategies that accommodate rather than challenge the fundamental nature of everwork, everwork environments may persist despite the negative consequences.